2019
DOI: 10.1111/den.13426
|View full text |Cite
|
Sign up to set email alerts
|

Novel submucosal injection solution 0.6% sodium alginate: Bench to market for endoscopic submucosal dissection optimization

Abstract: This Editorial refers to the article by N. Uemura et al., p 396–404 of this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Endoscopic treatments such as endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) are the most effective treatments in early-stage gastrointestinal neoplasms. The development of high-performance submucosal injection materials (SIMs) significantly contributes to the advancement of rapid and safe endoscopic treatments. ,, High-performance SIMs currently used in endoscopic treatments include sodium hyaluronate (HA), sodium alginate, hydroxypropyl methylcellulose, and other similar materials that are viscous solutions . In addition, to surpass the performance of current SIMs, various materials have been produced and their effectiveness as SIMs has been examined; these include shear-thinning hydrogels, biodegradable hydrogels, drug-eluting elastomeric polymers, and reverse-phase polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic treatments such as endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) are the most effective treatments in early-stage gastrointestinal neoplasms. The development of high-performance submucosal injection materials (SIMs) significantly contributes to the advancement of rapid and safe endoscopic treatments. ,, High-performance SIMs currently used in endoscopic treatments include sodium hyaluronate (HA), sodium alginate, hydroxypropyl methylcellulose, and other similar materials that are viscous solutions . In addition, to surpass the performance of current SIMs, various materials have been produced and their effectiveness as SIMs has been examined; these include shear-thinning hydrogels, biodegradable hydrogels, drug-eluting elastomeric polymers, and reverse-phase polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Currently employed SIMs such as HA, sodium alginate, and hydroxypropyl methylcellulose are Newtonian fluids. ,, Therefore, from a rheological viewpoint, the development of SIMs with pseudoplastic fluid characteristics can lead to the fabrication of SIMs having a better performance than the currently used SIMs.…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronic acid has been one of the most commonly used and reliable viscous solutions in the ESD procedure [30]. Recently, the usefulness of sodium alginate in the ESD procedure has been reported in Japan [31,32]. Furthermore, other viscous solutions have been explored to improve the ESD procedure in other (especially Western) countries [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The first inhuman application for gastric ESD was uneventfully conducted using various concentrations of SA eventually set at 0.6% of SA. 2 Uemura et al designed a multicenter randomized controlled trial and it has received an approval from the Ministry of Health, Labour, and Welfare of Japan for the marketing of medical devices and drugs, this study was registered with Pharmaceuticals and Medical Devices Agency. 3 Thus, on-label use of this drug would allow popularization in clinical practice in ESD through historical Japan Gastroenterological Endoscopy Society contribution and under ideal concept of the membership, that is a fruit of academic-industrial collaboration, highlighting the significance of preclinical animal studies using relative macrofauna or ex vivo simulation settings.…”
Section: Experimental and Translational Research In Endoscopic Submuc...mentioning
confidence: 99%
“…The ex vivo study showed equivalent thickness of the submucosal cushion with SA compared to sodium hyaluronate in the porcine stomach. The first in‐human application for gastric ESD was uneventfully conducted using various concentrations of SA eventually set at 0.6% of SA 2 . Uemura et al .…”
Section: Experimental and Translational Research In Endoscopic Submuc...mentioning
confidence: 99%